COMPLETE USE OF FOOD AS A MEASURE TO IMPROVE WASTE ACCUMULATION AND ENVIRONMENTAL IMPACTS (REMUNOM, 2024)
The consumer society is a term used to define a capitalist society that is advanced in the industrial development of mass production for mass consumption, having as its main characteristics the high level of production in proportion to exacerbated consumption. Environmental Education through full use is a way that has been used to alleviate the damage that nature has been suffering. In this way, this work aims to carry out a bibliographical review on the full use of food and consequent reduction in the disposal of usable parts of food.